Production of Bacterial Cellulose Aerogels With Improved Physico-Mechanical Properties and Antibacterial Effect - Revin, Viktor V.; Nazarova, Natalia B.; Tsareva, Ekaterina E.; Liyaskina, Elena V.; Revin, Vadim D.; Pestov, Nikolay A. (Frontiers in Bioengineering and Biotechnology, 2020)
Aerogels have gained significant interest in recent decades because of their unique properties such as high porosity, low density, high surface area, and excellent heat and noise insulation. However, their high cost and low mechanical strength limit their practical application. We developed appropriate conditions to produce aerogels with controlled density, high mechanical strength, and thermal characteristics from bacterial cellulose (BC) synthesized by the strain Komagataeibacter sucrofermentans H-110. Aerogels produced using TEMPO oxidized BC (OBC) exhibited high mechanical strength and lower shrinkage than those from native bacterial cellulose (NBC). Compared to the NBC, the use of TEMPO-oxidized BC with oxidation degrees (OD) of 1.44% and 3.04% led to the reduction of shrinkage of the aerogels from 41.02% to 17.08%. The strength of the aerogel produced from the TEMPO-oxidized BC with an oxidation degree of 1.44% was twice that of the aerogel produced from NBC. The addition of Mg2+at concentrations of 20 and 40 mM during the preparation of the aerogels increased the strength of the aerogels by 4.9 times. The combined use of TEMPO-oxidized BC and Mg2+ allowed pore size reduction from 1375 μm to 197.4 μm on the outer part of the aerogels, thereby decreasing the thermal conductivity coefficient from 0.036 to 0.0176 W/(m•K). Furthermore, novel biocomposites prepared from the aerogels based on NBC and OBC and sodium fusidate, which have high antibiotic activity against Staphylococcus aureus, were obtained. Owing to their antibacterial properties, these aerogels can be used as functional biomaterials in a wide range of applications such as in tissue engineering and fabrication of wound dressing materials.